PENINGKATAN PRESTASI KERJA MELALUI PENGEMBANGAN KARIR - Ipong Dekawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
In the current era of teachers as educators, it is not enough to be able to carry out their duties carrying out learning. But in the process of implementing these learning tasks must also excel if they do not want to compete in a career. Improving teacher work performance in carrying out learning is a necessity. There is a strong suspicion that career development is the dominant factor that drive work performance improvement. The focus of this study is to investigate the effect of career development on teacher work performance. The research approach is a mixture of quantitative and qualitative. Data collection techniques using a Likert scale questionnaire, of 72 teachers. Processing of research results using regression analysis techniques. The significance test uses the F-test. After carrying out and discussing the results of this study, the author can conclude that teacher career development has a positive and significant effect on teacher work performance. There are still several weaknesses in the management of career development, especially in terms of loyalty to institutions, networks and teacher work performance. So it is suggested that the opportunity for teachers to be consulted and do the work to the best of their ability be increased. Openness in measurement and performance systems, transparent in evaluating work performance and helping teachers to widen their networks in carrying out career development.